CHARACTERISTICS OF BREEDING PLACES OF ANOPHELES STEPHENSI IN A CITY ON PERSIAN GULF - A. Zaini; B. Djanbakhsh; AV. Manuchehri (Tehran University of Medical Sciences, 1975)
Breeding places of A. Stephensi were studied in Bandar Abbas city, on Persian Gulf to determine the characteristics of breeding places and the larval density. The conventional standard dipper was used and all stages in ten dippers were considered as measuring scales. The study showed the presence of larvae in seven different types of breeding places which were: Barrels and pounds which were used as water reservoirs for housing projects; Some pits produced as the result of break making activities; Water remaining in wash basins and bathrooms of summer houses; Some small drainers; Open water reservoirs in government buildings; Barrels used as water reservoirs in some of the huts; Shallow wells. Although in all of the above breeding places larval density was found to be high (550 per 10 dippers), adult mosquitoes were rare. However since people do not like malathion spraying of their houses because of its smell, larvae control seems to be the best alternative for malaria control of that area. Larvicides, draining of stagnant water and other means can be sued to lower both the larvae and adult anopheles populations.